Intention of the Meaning Qur'an as Nūr: The Implementation of Roland Barthes Semiotics on Qs. Al-Syūrā [42]:52: Intensi Makna Al-Qur’an Sebagai Nūr: Implementasi Semiotika Roland Barthes Terhadap Qs. Al-Syūrā [42]:52 - Syelviana, Ana (Aqwal: Journal of Qur'an and Hadis Studies, 2024)
Background and Objectives: Nūr is one of the Qur'an’s names reflecting its unique function and significance. While nūr generally means “light,” the Qur’an also uses Ḍiyā’, another word for light, though with a different nuance. This study aims to clarify why the Qur’an is called nūr and to explore its significance in guiding human life. Methodology: This literature-based research draws from books, journals, articles, and relevant written sources. Employing Roland Barthes’ semiotics, it conducts two levels of analysis: a linguistic analysis to determine the literal meaning of nūr in QS. Ash-Shura [42]:52 through dictionaries and various tafsīr; and a mythical analysis, examining contextual elements like verse type, historical background, and symbolic references. Main Findings: Nūr signifies a light possessing unique merit, while Ḍiyā’ denotes common illumination without the same distinction. Therefore, the Qur’an is called nūr to emphasize its exalted role. As nūr, the Qur’an serves as a guiding beacon, directing individuals toward truth and righteous conduct. Contributions: This study enriches tafsir literature by clarifying the Qur’an’s purpose as nūr, particularly in QS. Ash-Shura [42]:52. Conclusion: Nūr represents Allah’s power to influence human hearts, guiding them from the darkness of error and immorality to the brightness of faith and virtuous deeds. By fostering a morally upright society, the Qur’an as nūr contributes to peace and harmony in human life